2007
DOI: 10.3174/ajnr.a0700
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of Normal-Appearing White Matter in Mild Cognitive Impairment and Early Alzheimer Disease: Preliminary Evidence of Axonal Degeneration in the Temporal Lobe

Abstract: BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) is a sensitive technique for studying cerebral white matter. We used DTI to characterize microstructural white matter changes and their associations with cognitive dysfunction in Alzheimer disease (AD) and mild cognitive impairment (MCI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(156 citation statements)
references
References 50 publications
12
138
4
1
Order By: Relevance
“…The involvement of this tract as well as the CC, fornix, perforant path, and temporal WM is consistent with previous findings from DTI studies that reported diffusivity increases or anisotropy decreases in the same set of WM areas (Fellgiebel et al, 2004;Medina et al, 2006;Xie et al, 2006;Huang et al, 2007;Teipel et al, 2007;Zhang et al, 2007). Atrophy of the CC and perforant path have also already been highlighted in previous VBM studies of AD (Chaim et al, 2007) and MCI (Stoub et al, 2006), respectively.…”
Section: Discussionsupporting
confidence: 79%
“…The involvement of this tract as well as the CC, fornix, perforant path, and temporal WM is consistent with previous findings from DTI studies that reported diffusivity increases or anisotropy decreases in the same set of WM areas (Fellgiebel et al, 2004;Medina et al, 2006;Xie et al, 2006;Huang et al, 2007;Teipel et al, 2007;Zhang et al, 2007). Atrophy of the CC and perforant path have also already been highlighted in previous VBM studies of AD (Chaim et al, 2007) and MCI (Stoub et al, 2006), respectively.…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown to be susceptible to atrophy in AD, mainly as a correlate of wallerian degeneration of commissural nerve fibers of the neocortex. 25,27 It is generally assumed that there is a topographic arrangement of axons within the CC, according to their origin, that could justify its texture differences in healthy controls and patients with AD, whose callosal atrophy might be restricted just to axons proceeding from atrophic temporal structures, for example, as shown in a diffusion tensor study by Huang et al 35 In fact, our study found significant differences among the 3 groups for the CC (Table 1), in 6/44 texture parametersnamely, the contrast (for distances 1 and 2) and difference variance (for all distances) parameters. It is better to have fewer significant parameters because in an ideal situation, we would like to have a unique descriptor extracted from the images that could indicate the presence or absence of tissue alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal DT derived indices have also been demonstrated in frontal region, and specifically in the cingulum posterior, corpus callosum, fasciculus longitudinalis superior, and fasciculus uncinatus [193][194][195].…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%